Mindfulness Meditation Biases Visual Temporal Order Discrimination but Not Under Conditions of Temporal Ventriloquism - Tian, Yue; Liu, Xinghua; Chen, Lihan (Frontiers in Psychology, 2020)
This study examined how cognitive plasticity acquired from a long (8 weeks) course of mindfulness training can modulate the perceptual processing of temporal order judgment on a sub-second scale. Observers carried out a temporal order judgment (TOJ) on two visual discs, with or without concurrent paired beeps. A temporal ventriloquism paradigm was used in which the sound beeps either were synchronized with the two discs or bracketed the visual stimuli by leading the first disc by 50 ms and lagging the other by 50 ms. A left-to-right bias in TOJ was found under the visual-only condition after mindfulness training. This bias was positively correlated with “acting with awareness”, a factor in the Five Facet Mindfulness Questionnaire, showing that awareness of every moment and enhanced attention focus magnifies the left-to-right bias. However, the effect of mindfulness training may be short-lived and was not present when attention was diverted by auditory events in the cross-modal temporal ventriloquism illusion.